[Formula Omitted] Reliable Bumpless Transfer Control for Switched Systems With State and Rate Constraints - Zhao, Ying; Zhao, Jun (IEEE transactions on systems, man, and cybernetics. Systems, 2020)
This paper concentrates on the issue of [Formula Omitted] reliable bumpless transfer control for a category of switched systems (SSs) with state and rate constraints. The [Formula Omitted] reliable bumpless transfer control problem refers to designing a collection of reliable controllers and a switching rule to ensure the SSs to satisfy the bumpless transfer performance and [Formula Omitted] reliable property. First, a concept of the bumpless transfer performance for a system in this category with possible actuator faults is introduced. Then, by a multiple Lyapunov functions approach, a switching rule and a set of reliable controllers are co-designed to assess the disturbance tolerance capability with bumpless transfer performance and to solve the [Formula Omitted] reliable bumpless transfer control problem of the system. Second, a criterion guaranteeing the bumpless transfer performance and [Formula Omitted] reliable property of the system is established. The criterion allows each subsystem not to possess both the bumpless transfer performance and [Formula Omitted] reliable property. Further, an algorithm is proposed to estimate the attraction domain of the system without disturbances. Finally, the effectiveness of the presented control scheme is verified by an example of controlling a turbofan model.